Eight year old male with autism spectrum disorder and associated hematuria and nephrolithiasis - Willson, Emily; Stoicescu, Lavinia; Seshadri, Kapila (International Journal of Contemporary Pediatrics, 2016)
This is the case of an 8-year-old male of Egyptian descent, with Autism Spectrum Disorder and associated hematuria and nephrolithiasis. A few relevant case reports of children with autism and comorbid nephrolithiasis have been reported. His case is being reported to draw attention to this particular comorbidity, which may cause other clinicians to report similar cases, and generate an interest in further exploring the renal comorbidities/metabolic correlates of autism.